2011
DOI: 10.1063/1.3552686
|View full text |Cite
|
Sign up to set email alerts
|

All-printed infrared sensor based on multiwalled carbon nanotubes

Abstract: International audienceThis contribution deals with all-printed infrared sensors fabricated using multiwalled carbon nanotubes deposited on a flexible polyimide substrate. A high responsivity of up to 1.2 kV/W is achieved at room temperature in ambient air. We evidence a strong dependence of the device transduction mechanism on the surrounding atmosphere, which can be attributed to bolometric effect interference with water molecule desorption upon irradiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The optical properties of CNTs help to understand their structure [ 14 ], evaluate their purity [ 15 ] and open new applications for optical sensing [ 16 , 17 ]. MWCNT-based infrared detectors have received much attention due to MWCNT band gap of 0.4–6.0 eV and high absorption efficiency in IR [ 18 ]. A bolometer based on CNT/polymer composites was constructed for the detection of infrared radiation from the range 0.2–20 μm [ 19 ] and it was shown that the sensitivity and response time of the CNT-based bolometers can be substantially improved by an appropriate functionalization and selection of organic matrix [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optical properties of CNTs help to understand their structure [ 14 ], evaluate their purity [ 15 ] and open new applications for optical sensing [ 16 , 17 ]. MWCNT-based infrared detectors have received much attention due to MWCNT band gap of 0.4–6.0 eV and high absorption efficiency in IR [ 18 ]. A bolometer based on CNT/polymer composites was constructed for the detection of infrared radiation from the range 0.2–20 μm [ 19 ] and it was shown that the sensitivity and response time of the CNT-based bolometers can be substantially improved by an appropriate functionalization and selection of organic matrix [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 When used as radiation detectors, CNTs show wide absorbance and large photoresponse in the infrared spectral regime although a clear understanding of its origin is still not known. 16 For semiconductor CNTs, the band gap energy has values in the range of 0.4 eV and 6.0 eV, 17 there is an inverse relationship between the nanotubes diameter and band gap energy. The electronic configuration of CNTs depends on contribution from each individual shell making up the MWCNT structure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the electronic structures and optoelectronic properties of SWCNTs are strongly affected by the surface oxygen, which leads to a slow photoresponse (30–60 ms) in accordance with the oxygen adsorption/desorption on the SWCNT surface . MWCNTs may present an alternative to SWCNTs with advantages in ease of the dispersion, much reduced contribution of the surface oxygen, enhanced light absorption per tube, highly anisotropy of charge conduction, and lower cost (no purification is needed) . Particularly, MWCNTs have smaller exciton binding energy due to their larger diameters with respect to their SWCNTs counterpart's, which means that the requirement for a large band‐edge offset is considerably reduced.…”
mentioning
confidence: 99%